Genome-Wide Association Study Reveals Novel Loci for SC7 Resistance in a Soybean Mutant Panel - Che, Zhijun; Liu, Hailun; Yi, Fanglei; Cheng, Hao; Yang, Yuming; Wang, Li; Du, Jingyi; Zhang, Peipei; Wang, Jiao; Yu, Deyue (Frontiers in Plant Science, 2017)
Soybean mosaic virus (SMV) is a member of Potyvirus genus that causes severe yield loss and destroys seed quality in soybean (Glycine max (L.) Merr.). It is important to explore new resistance sources and discover new resistance loci to SMV, which will provide insights to improve breeding strategies for SMV resistance. Here, a genome-wide association study (GWAS) was conducted to accelerate molecular breeding for the improvement of resistance to SMV in soybean. A population of 165 soybean mutants deprived from two soybean parents was used in this study. There were 104 SNPs identified significantly associated with resistance to SC7, some of which were located within previous reported quantitative trait loci. Three putative genes on chromosome 1, 9 and 12 were homologous to WRKY72, eEF1Bβ and RLP9, which were involved in defense response to insect and disease in Arabidopsis. Moreover, the expression levels of these three genes changed in resistance and susceptible soybean accessions after SMV infection. These three putative genes may involve in the resistance to SC7 and be worthy to further research. Collectively, markers significantly associated with resistance to SC7 will be helpful in molecular marker-assisted selection for breeding resistant soybean accessions to SMV, and the candidate genes identified would advance the functional study of resistance to SMV in soybean.